Inverse of an Arbitrary Vandermonde Matrix - López-Bonilla, J.; Vidal-Beltrán, S.; Rivera-Rebolledo, J.M. Rivera (Journal of the Institute of Engineering, 2011)
It is shown a general formula to invert any type Vandermonde matrix. Key words: Arbitrary Vandermonde DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5120 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 263-265 Uploaded Date: 20 July, 2011